Comparative echocardiographic features of conditions presenting with symptomatic pulmonary hypertension and right ventricular hypertrophy in early infancy. Issue 1 (July 1980) - Patel, R; Rowland, D; Bloom, K R; Williams, C M; Rowe, R D
Abstract : Echocardiographic dimensions in infants (less than 2 months) with pulmonary hypertension, associated with coarctation of the aorta in 21, total anomalous venous return in 10, and left-to-right shunts in 14 were compared with 10 infants with respiratory distress syndrome, seven with transient tachypnoea of the newborn, 20 normal children, and with each other. Distinguishing features of total anomalous pulmonary venous return were very significantly lower left atrial and left ventricular dimensions. Right ventricular enlargement was maximal in patients with coarctation of the aorta and total anomalous pulmonary venous return. Left ventricular end-diastolic dimension in coarctation of the aorta was not significantly different from normal but the left ventricular end-systolic dimension was significantly lower, suggesting a hypercontractile left ventricle. Similar findings were observed in patients with left-to-right shunts. M-mode echocardiograms are hence valuable in differentiating conditions which may present with intractable congestive cardiac failure in the newborn and also distinguishing them from common respiratory disease of the neonate.